Candida-Reactive T Cells for the Diagnosis of Invasive Candida Infection—A Prospective Pilot Study - Koehler, Felix C.; Cornely, Oliver A.; Wisplinghoff, Hilmar; Schauss, Astrid C.; Salmanton-Garcia, Jon; Ostermann, Helmut; Ziegler, Maren; Bacher, Petra; Scheffold, Alexander; Alex, Regina; Richter, Anne; Koehler, Philipp (Frontiers in Microbiology, 2018)
Background Blood or tissue culture or histology prove invasive Candida infection, but long time to result, limited feasibility and sensitivity call for new approaches. In this pilot project, we describe the diagnostic potential of quantitating Candida-reactive, CD4/CD69/CD154 positive lymphocytes in blood of patients with invasive Candida infection. Methods We used flow cytometry quantitating Candida-reactive, CD4/CD69/CD154 positive lymphocytes from peripheral blood of patients with invasive Candida infection, from patients at risk and healthy volunteers as controls. Results Elevated levels of Candida-reactive lymphocytes were measured in 13 patients with proven invasive Candida infection and in one patient with probable hepatosplenic candidiasis. Results of three candidemia patients were uninterpretable due to autofluorescence of samples. Twelve of 13 patients had Candida identified to species level by conventional methods, and T cell reactivity correctly identified Candida species in 10 of 12 patients. Nine hematological high-risk patients and 14 healthy donors had no elevated Candida-reactive T cell counts. Conclusions This Candida-reactive lymphocyte assay correctly identified the majority of patients with invasive Candida infection and the respective species. Our assay has the potential to support diagnosis of invasive Candida infection to species level and to facilitate tailored treatment even when biopsies are contraindicated or cultures remain negative.